Prayer Content Analysis: Understanding Prayer Language in the Context of Ethical Decision-Making - Roragaba, Yeni Irawati; Maahury, Yane R. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to examine the use of language in prayer in relation to ethical decision-making within the GKI Klasis Waibu Moi congregation. The problem explored is how prayer language affects ethical decisions, considering that prayer is often viewed as a monotonous routine that can lead to spiritual dryness. The research method employed is descriptive qualitative, analyzing data from prayer recordings. Data collection involved documenting prayer recordings, which were then transcribed, reduced, presented in tables, and analyzed. Data analysis utilized Miles and Huberman's method. The results indicate that prayer language plays a crucial role in reflection and meditation, petitions, and the expression of spiritual values. Prayers involving deep reflection, sincere petitions, and expressions of values such as humility, love, honesty, justice, and hope significantly impact ethical decision-making and strengthen the spiritual relationship with God.